2012
DOI: 10.1017/s1478951512000417
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, race, and advance directives in an inpatient palliative care consultation service

Abstract: This study demonstrates the impact of a PCC on the completion of advance directives, on both whites and nonwhites. The PCC Intervention significantly reduced differences between whites and African Americans in completing advance directives, which have been consistently documented in the end-of-life literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 24 publications
0
53
2
Order By: Relevance
“…Attributes of patient population availing a serviceRecord reviews can also analyse the characteristics of subjects attending a particular treatment service; both inpatient, as well as outpatient [26]. This may help in guiding policies and making amendments to the services provided, keeping in view the features of the clinical populations served.…”
Section: Applications Of Record Reviewsmentioning
confidence: 99%
“…Attributes of patient population availing a serviceRecord reviews can also analyse the characteristics of subjects attending a particular treatment service; both inpatient, as well as outpatient [26]. This may help in guiding policies and making amendments to the services provided, keeping in view the features of the clinical populations served.…”
Section: Applications Of Record Reviewsmentioning
confidence: 99%
“…People with non-Christian religions may have other opinions on end-of-life care and palliative sedation. 22 Secondly, an internet panel may involve selection bias. To minimise this bias, an existing panel consisting of a randomised sample of people (thus not self-selected) was used, which enabled all selected members to participate (no restriction to internet users only).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…11,12 In addition, studies have shown that IPC services reduce the likelihood of intensive care unit (ICU) readmission. [13][14][15] There is, however, scant evidence supporting ongoing cost savings for those patients who survive to discharge.…”
Section: Introductionmentioning
confidence: 99%